EFFECT OF COW MANURE ON THE GROWTH AND CROP PRODUCTION OF WATERMELON (Citrullus lanatus) - Rivanly Sambelorang; Jemmy Nayoan (Sam Ratulangi University, 2020)
Watermelon plants are widely cultivated by people, especially in the lowlands, so that they provide many benefits to watermelon farmers and entrepreneurs, and can improve the improvement of the Indonesian economy, especially in agriculture. Watermelon cultivation increases farmers' income. The attraction of watermelon cultivation for farmers lies in its high economic value. Some of the advantages of watermelon farming include its relatively short life. Special for around 70-80 days, it can be used as intercropping plants in paddy fields during the dry trend. Watermelon production has a fast prospect in the country. Based on the Central Statistics Agency the development of watermelon production in Indonesia in 2009 reached 474,327 tons.Keywords: fertilize., cultivation., watermelon. Abstrak Tanaman semangka dibudidayakan secara luas oleh masyarakat terutama di dataran rendah, sehingga memberi banyak keuntungan kepada petani dan pengusaha semangka, serta dapat meningkatkan perbaikan tata perekonomian Indonesia, khususnya bidang pertanian. Budidaya tumbuhan semangka meningkatkan pendapatan petani. Daya tarik budidaya semangka bagi petani terletak pada nilai ekonominya yang tinggi. Beberapa kelebihan usahatani semangka diantaranya yaitu berumur relatif singkat. Istimewa untuk sekitar 70-80 hari, sanggup dijadikan tumbuhan penyelang di lahan sawah pada trend kemarau. Hasil produksi Semangka mempunyai prospek yang pesat di dalam negeri. Berdasarkan Badan Pusat Stastistik perkembangan produksi tanaman semangka di Indonesia tahun 2009 mencapai 474.327 ton.Kata kunci: pupuk., budidaya., semangka.